La terapia ocupacional para mejorar la calidad de vida en los adultos mayores, que asisten al centro de atención para el adulto mayor Los Arupos, de la ciudad de Loja, en el periodo comprendido 2013-2014 - Aguirre Cueva, Luz Elena (2015)
This research called The Occupational Therapy to improve the Quality of Life in Older Adults, attending Care Center for the Elderly The Arupos, City of Loja, in the period 2013-2014. The purpose for which it is governed Develop occupational therapy to improve the quality of life in older adults, for the same descriptive and social action design was used; - qualitative and descriptive analytical, hermeneutical, quantification: where the following methods were discussed. From a population of 22 seniors was taken as selective sample to 5 of them. The results were based on a diagnosis, implementation and validation of the study variables. After obtaining the results we conclude that most adults over the center managed to maintain a good quality of life and in other cases it was improved. Therefore it is recommended to perform activities such as dancing, music, singing, memory exercises, physical and recreational activities, including occupational therapy activities that manage to maintain or improve the quality of life in the town of Aging.